Quality Assessment of Fried Oils from Different Street Food Vendors and Restaurants in Different Areas of Gilgit, Pakistan: Cooking Oil Quality in Northern Areas of Pakistan - Haider, Sara; Akhtar, Aqsa; Khalid, Nauman (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The study was designed to estimate the quality of the frying oils used in northern areas of Pakistan. A cross-sectional analysis was performed to investigate the behavior and common practices of street food vendors (SFVs) regarding oil selection, food preparation, and awareness of rancid oil on human health. Seventy-Eight (78) commercial fried oil samples were evaluated based on the free fatty acid (FFAs), peroxide value (PV), moisture contents (MC), total polar matter (TPM), color, and iodine value (IV). The analysis showed that FFAs, PV, TPM, color, and IV significantly deviated from standard values provided by Pakistan Standard Quality Control Authority, (PSQCA) Pakistan. The SFVs used low-quality oil because of low price and ease of availability over quality, frying oil was changed infrequently and blended with new oil. Furthermore, the majority of SFVs were unaware of the hazards of rancid oil to human health, food handling practices were unsanitary, and cleaning methods were ineffective. Quality control, legislation, and SFVs safety and hygiene training are the most critical requirements to improve the overall quality of fried street foods in Gilgit, Pakistan.